1995
DOI: 10.1093/bja/74.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of four i.v. anaesthetic agents on polymorphonuclear leucocyte function

Abstract: Initial resistance of bacterial infection is mediated primarily by polymorphonuclear leucocytes (PMN). Anaesthetic agents have been reported to impair various aspects of PMN function. It is possible that the use of these agents to sedate critically ill patients may further compromise an already depressed host defence mechanism. A flow cytometric technique with fresh whole blood from 10 healthy volunteers was used. Phagocytic and respiratory burst activity of PMN incubated for 1 h with either propofol, thiopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 24 publications
2
37
0
1
Order By: Relevance
“…Propofol impairs the chemotaxis and respiratory burst of neutrophils in response to fMLF (12,13). However, other research revealed that propofol fails to alter respiratory burst in PMA-activated neutrophils (14). Indeed, the cellular mechanisms responsible for the pharmacological effects of propofol in human neutrophils are controversial and remain to be established.…”
mentioning
confidence: 99%
“…Propofol impairs the chemotaxis and respiratory burst of neutrophils in response to fMLF (12,13). However, other research revealed that propofol fails to alter respiratory burst in PMA-activated neutrophils (14). Indeed, the cellular mechanisms responsible for the pharmacological effects of propofol in human neutrophils are controversial and remain to be established.…”
mentioning
confidence: 99%
“…Nishina et al (1998) found that thiopental, midazolam and ketamine impaired chemotaxis, phagocytosis and oxygen radicals production. The results of Duncan and Cullen (1977) and Davidson et al (1995) suggest that halothane, propofol, thiopentone, midazolam and ketamine have minimal effects on phagocytosis, only extremely high and clinically irrelevant concentrations of thiopentone and ketamine may affect phagocytic function. Alteration of phagocytic abi lity was found in animals in the study by Paulík et al (1999) after excision of skin papillomas in calves using anaesthesia with xylazine and procaine.…”
Section: Discussionmentioning
confidence: 99%
“…The depression of cell-mediated immunity can develop in various degrees and is usually dependent on the kind of anaesthetic, its dose and on the extent of surgical trauma. Various anaesthetics (propofol, thiopentone, midazolam, ketamine) are known to depress human neutrophil functions (Salo, 1989;Davidson et al, 1995;Mikawa et al, 1998;Nishina et al, 1998). Depression of lymphocyte function was studied after the use of thiopentone, methohexitone, etomidate, and pheno-Acta Veterinaria Hungarica 51, 2003 barbitone (Puppo et al, 1980;Devlin et al, 1994).…”
mentioning
confidence: 99%
“…In healthy volunteers, thiopentone and etomidate impair lymphocytes function [84]. Thiopentone may have no effect on IL-2 [93], but it decreases INF-y [93,98], IL-4 [93] and INF-y/IL-4 ratio [93], and impairs chemotaxis [99] and phagocytosis [88, 99,100]. Similarly, midazolam inhibits chemotaxis [99] and IL-8 secretion [90].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%